Graham and Dodd's security analysis - Graham, Benjamin 1894-1976 (McGraw-Hill Book Company, 1988)
Maintaining the high standards of prior editions, Security Analysis puts at your fingertips the authoritative guidance on analyzing securities that generations of investment bankers have come to rely on.